Konstruksi Ring Bersih dari Sebarang Ring - Sari, Kartika; Wijayanti, Indah Emilia (Jurnal Matematika; Vol 5 No 2 (2015), 2015)
The aims of this research was to construct a clean ring from any ring.  The base on the fact  that the endomorphism ring of every pure-injective module is clean, it was constructed a clean ring from any ring. So, the result of this research was it always could be constructed a clean ring from any ring.
Keywords: construct; a clean ring; pure-injective module